Achieving superior strength-ductility synergy by constructing network microstructure in Ti-based high-entropy alloy matrix composites. (December 2022) - Wang, Cunyu; An, Qi; Huang, Lujun; Zhang, Rui; Chen, Xin; Chen, Run; Geng, Lin; Peng, Hua-Xin
Abstract: In-situ (Ti, Nb)B whiskers ((Ti, Nb)Bw) reinforced Ti-based high-entropy alloy (HEA) matrix composites ((Ti, Nb)Bw/Ti1.5 ZrNbAl0.3 ) with a quasi-continuous network microstructure were successfully fabricated via low energy milling (LEM) and hot-pressed sintering (HPS). The results show that the in-situ (Ti, Nb)Bw reinforcements were distributed around Ti1.5 ZrNbAl0.3 matrix particle forming a special network architecture. This microstructure resulted in remarkable grain refinement of Ti-based HEA matrix, which contributed to the superior strength-ductility synergy. Consequently, the as-sintered (Ti, Nb)Bw/Ti1.5 ZrNbAl0.3 composites exhibited a high yield strength (σYS = 1015 MPa) while maintaining superior ductility (ϵe = 17.5%), which were simultaneously increased by 11.5% and 96.6% compared with the monolithic Ti1.5 ZrNbAl0.3 alloy. The network microstructure design of HEA-based composites could be therefore exploited to overcome the strength-ductility trade-off. Graphical abstract: Image 1 Highlights: The novel HEA matrix composites with quasi-continuous network microstructure were successfully fabricated. The (Ti, Nb)Bw/Ti1.5 ZrNbAl0.3 composites possess excellent mechanical properties. The network microstructure design could be exploited to overcome the strength-ductility trade-off.